Effectiveness Of The Marzano And Therese Models In The Achievement Of Grammar Among Literary Students - Ghayyib, Natiq Saeed (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This research investigated the effectiveness of the Marzano and Therese models in achieving grammar among literary students. In this study, the researcher selected three preparatory schools for boys, such as Ali bin Abi Talib Primary School, to achieve the aim of the study. The sample included (32) students from Ali bin Abi Talib Preparatory School, (32) students from Abu Hanifa al-Numan Preparatory School, and (31) students from Al-Miqdadiya Primary School. This study used the Marzano model, which was applied to the first experimental group. The researcher designed equal groups with partial control and prepared teaching plans and the multiple-choice test for the three groups. The number of test items was (30, in which appropriate statistical methods were used to conduct the research. The results of the research showed the superiority of the second experimental group that studied according to Therese model over the first experimental group studied according to the model and over the control group that studied traditionally, the superiority of the experimental group that looked traditionally, and the superiority of the experimental group over the control group in the post achievement test.